Dynamic reduction of rock mass mechanical parameters based on numerical simulation and microseismic data – A case study. (January 2019) - Zhao, Yong; Yang, Tianhong; Yu, Qinglei; Zhang, Penghai
Highlights: Damage coefficient was established based on multiple source parameters and reliability analysis theory. The failure process and failure mechanism were analyzed using source parameters and moment tensor. The rock mass mechanical parameters were modified dynamically. Shear strength and shear failure elements changing with time were analyzed by numerical simulation. Abstract: Rock mass mechanical parameters change dynamically over time and space, and this process is accompanied by the release of seismic signals. With the aid of microseismic (MS) monitoring, the temporal, spatial and intensity source parameters that can reflect the rock mass damage were extracted from MS data, and the rock mass damage coefficient based on MS multiple source parameters was established. Taking Shirengou Iron Mine as a test site, discontinuity scanning was carried out, and the size of the representative elementary volume (REV) was obtained by analyzing the change of the joint mass density P 32 with different lengths of the statistical cube. According to the spatial-temporal variation of source parameters that were used to construct the damage coefficient, the failure process and mechanisms were analyzed and the failure period was divided into five stages. The damage coefficient of each REV was calculated on the basis of the MS data combined with the rock mass damage, and the damage process in the rock mass failure process was also analyzed. Then, the REV damage coefficients in different time periods were embedded into the FLAC 3D computing program as inputs, and with the combination of the reduction formula, the rock mass mechanical parameters were dynamically modified. Taking shear strength as a representative property, the shear strength changes in different time periods were analyzed. In addition, the change of rock mass shear failure zones was analyzed. By combining the rock mass damage coefficient established by multiple source parameters with numerical simulation, the dynamic reduction of rock mass mechanical parameters can be realized, providing a new quantitative analysis method for dynamic evaluation of rock mass stability.